Pengaruh literasi Keuangan dan Perilaku Keuangan Terhadap Manajemen Keuangan Mahasiswa Kelas Karyawan - Achmad Nuruddin; Andi Cahya Putra; Tri Yani; Rayhan Gunaningrat (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the effect of financial literacy and financial behavior on the implementation of financial management. The study uses a quantitative approach with a survey method involving 54 respondents. The data were analyzed using multiple linear regression after undergoing classical assumption tests, including normality, multicollinearity, and autocorrelation tests. The test results show that the regression model meets all classical assumptions. The coefficient of determination (R Square) value of 0.832 indicates that financial literacy and financial behavior can explain 83.2% of the variation in the implementation of financial management. The simultaneous test results show that financial literacy and financial behavior together have a significant effect on the implementation of financial management. However, partially, only financial behavior has a positive and significant effect, while financial literacy does not show a significant effect. These findings indicate that the implementation of financial management is more influenced by actual individual behavior than by the level of financial knowledge alone. This study emphasizes the importance of a behavioral finance approach in improving the quality of individual financial management.